2011
DOI: 10.1186/1471-2458-11-406
|View full text |Cite
|
Sign up to set email alerts
|

Disability pension by occupational class - the impact of work-related factors: The Hordaland Health Study Cohort

Abstract: BackgroundThe social gradient in disability pension is well recognized, however mechanisms accounting for the gradient are largely unknown. The aim of this study was to examine the association between occupational class and subsequent disability pension among middle-aged men and women, and to what extent work-related factors accounted for the association.MethodsA subsample (N = 7031) of the population-based Hordaland Health Study (HUSK) conducted in 1997-99, provided self-reported information on health and wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
68
0
6

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(79 citation statements)
references
References 36 publications
5
68
0
6
Order By: Relevance
“…Therefore, one should be careful with generalizing the current findings from the Netherlands to other countries with different welfare state regimes (40). However, as described earlier, socioeconomic differences in labor force exit have also been found in other European studies (9,11,15,17).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Therefore, one should be careful with generalizing the current findings from the Netherlands to other countries with different welfare state regimes (40). However, as described earlier, socioeconomic differences in labor force exit have also been found in other European studies (9,11,15,17).…”
Section: Discussionmentioning
confidence: 62%
“…A low level of education, occupational status, and income seem to be strong determinants of disability in both genders (9)(10)(11)(12)(13)(14). A recent Norwegian study (15) showed that there was a socioeconomic gradient in disability pension corresponding to socioeconomic gradients in health.…”
mentioning
confidence: 99%
“…Studies also show a clear negative association between socioeconomic status and disability pension (Allebeck & Mastekaasa, 2004;Bjørn-gaard et al, 2009). The risk of disability pension is higher in groups with low education (Bruusgaard, Smeby, & Claussen, 2010;Johansson, Leijon, Falkstedt, Farah, & Hemmingsson, 2012) or low socioeconomic status (Haukenes, Mykletun, Knudsen, Hansen, & Maeland, 2011;Østby, Ørstavik, Knudsen, ReichbornKjennerud, & Mykletun, 2011). Ross and Wu (1995) point to three categories of explanations for the relationship between education and health: (a) work and economic conditions (e.g., employment, full-time jobs, income, economic hardship), (b) social-psychological resources (e.g., personal control, social support), and (c) health-related aspects of lifestyle (e.g., exercise, alcohol consumption, smoking, preventive medical care).…”
Section: Disability Pension and Previous Research On Predictorsmentioning
confidence: 99%
“…Von sozialpolitischem Interesse ist zudem, dass bei der krankheitsbedingten Frühberentung eine Ungleichverteilung je nach beruflicher Position registriert wird. Bödeker et al 2006 [18] zeigten bspw. anhand von Routinedaten der Deutschen Rentenversicherung, dass gering qualifizierte Berufe sowohl im Dienstleistungs-als auch im produktiven Sektor erhöhte krankheitsbedingte Früh-berentungsraten mit sich bringen [18].…”
unclassified
“…Bödeker et al 2006 [18] zeigten bspw. anhand von Routinedaten der Deutschen Rentenversicherung, dass gering qualifizierte Berufe sowohl im Dienstleistungs-als auch im produktiven Sektor erhöhte krankheitsbedingte Früh-berentungsraten mit sich bringen [18]. Auch diese Beobachtung beschränkt sich nicht auf Deutschland [19][20][21][22].…”
unclassified